Intergenerational Social Mobility among Muslim Minority in Kerala State of India: Formal and Religious Education - Sreekala Edannur; Afsal PK and Susan D.Myers (Journal of Education & Social Policy, 2014)
This study compares social mobility of Muslims in Kerala across two generations with regard to education, occupation and gender. It also tries to find out the relationship of religious education with formal education among younger generation. Data from 231 randomly selected Muslim respondents; 128 males and 103 females, aged 25-40 from twelve election wards of 6 Panchayats in Malappuram district of Kerala state is used for the study. Respondents aged 25 to 40 were selected from the Socio Economic and Caste Census 2011. The results of the study show high upward intergenerational educational mobility and strong occupational reproduction among Muslim community in Kerala. Family background influences the chances of education and occupation of younger generation. Religious education is not found hindering the formal education of the younger generation of Muslims in Kerala.